Obsessive‐compulsive disorder and men's health. Part 1: Recognition and diagnosis. Issue 1 (18th January 2023) - Conti, Dario; Pellegrini, Luca; Riaz, Maham; Mpavaenda, David; Sim, Alex; Fineberg, Naomi
Abstract : Obsessive‐compulsive disorder (OCD) commonly affects males and can manifest with a range of urological symptoms directly linked to the content of the OCD, including urinary urgency, urinary frequency, urinary retention and sexual dysfunction. Accurate recognition of OCD in such cases is fundamental to avoid misdiagnosis, risks to patients associated with untreated OCD (including suicidal behaviour), unnecessary physical health investigations and delayed treatment. In Part 1 here, the authors discuss the recognition and diagnosis of OCD. Part 2 will consider its treatment.